Estudo da ação do tabaco na circulação cerebral por meio da análise Dopller das artérias cerebrais médias e oftálmicas em fumantes crônico - Paes, Maria Marta Bini Martins e (2016)
Objectives: To evaluate the mean of Doppler velocities and indices of the Middle Cerebral Arteries (MCA) and Ophthalmic Arteries (OA) in chronic smokers according to the time of cigarette consumption as a function of sex. To evaluate the relations between the Middle Cerebral Artery and the Ophthalmic Artery. Methods: We used the Doppler method for assessing the Peak of Velocity Systolic (PVS), End Diastolic Velocity (EDV) and Mean Velocity (VM) in MCA and OA. MV was collected in the Internal Carotid Artery (ICA) to perform the Lindegaard Index (IL). Resistance Index (RI) and Pulsatility Index (IP) were performed in both arteries. Second Peak of Systolic Velocity (P2) and P2 / PVS (Peak Ratio _ PR) were evaluated only in the AO. The samples were collected with a minimum of two hours of cigarette withdrawal (late period) and up to 10 minutes after smoking (recent period). We used the paired t-test for the comparison between late and recent periods of cigarette consumption (intragroup assessment) and the unpaired t-test for the comparison between sexes (intergroup comparison). The difference between the late and recent period were expressed in percentages for the evaluation of the effect on the AO and the MCA were used. The variation between intra-arterial velocities in the AO and in the ACM was estimated using the ANOVA and Krukal-Walis tests. We considered significance at a level of α ≤ 0.05 and a 95% confidence interval for all tests. Results: The study group was composed by 71 chronic smokers (34 men and 37 women). The PVS, EDV and VM showed a velocity increase in OA and MCA in both sexes after smoking. RI and PI presented a decrease in both Arteries after smoking, with effect almost exclusively in women. PR was not changed after consumption of cigarettes in both sexes, but it was higher in women in both periods of consumption. There was no variation of IL. Conclusions: There was an increase in flow velocities after cigarette consumption in both arteries and sexes, presenting the same direction of effect, compatible with transient and functional alterations in the arterial bed. However, the findings suggest that women have a greater hemodynamic response to cigarette smoking.